CLINICAL MANIFESTATIONS AND OUTCOMES OF RETINAL HEMORRHAGES IN INFANTS: A CASE SERIES - Ludmila V. Kogoleva; Elena N. Demchenko ("Paediatrician" Publishers LLC, 2018)
Background. Retinal hemorrhages in infants are frequent pathologies, but their causes, clinical forms and functional outcomes are poorly studied. The study of hemorrhage localization in the eye structure, time frames of their resolution, and the long-term effects that may affect the development of vision is of particular interest.Objective. Our aim was to analyze clinical forms, time frames of resolution and long-term clinical and functional outcomes of retinal hemorrhages in infants.Methods. All children with retinal hemorrhages, who applied to a premature baby room in the MRI of ED n. a. Helmholtz at the age from 3 weeks to 3 months for 5 years (2011-2015), were examined using indirect ophthalmoscopy. In case of extensive lesions, the process dynamics was controlled by a pediatric digital retinal imaging system. Long-term clinical and functional outcomes of retinal hemorrhages were studied using ultrasound examination and spectral optical coherence tomography.Results. Fundus hemorrhages were revealed in 108 (5.9%) of 1,825 infants on 142 eyes (34 children had bilateral hemorrhages). Hemorrhages were more frequent in children delivered vaginally (79 children, 73.2%), were unilateral (74 children, 63.5%), pre-retinal (108 eyes, 76.1%), of central localization (119 eyes, 83.8%). The time frames of hemorrhage resolution in 53 children (49.1%) were more than one month. Long-term outcomes of retinal hemorrhages were studied in 22 children (33 eyes) at the age of 2-5 years. Residual changes in the structure of the neuroepithelium and vitreoretinal interface with a decrement in visual acuity were noted in 7 children (9 eyes).Conclusion. Retinal hemorrhages of newborns are characterized by clinical polymorphism, different time frames of resolution and outcomes, which requires a case follow-up.